Image-guided high-dose-rate brachytherapy of head and neck – a case series study - Cisek, Paweł; Kieszko, Dariusz; Brzozowska, Anna; Kordzińska-Cisek, Izabela; Mazurkiewicz, Maria (Journal of Contemporary Brachytherapy, 2016)
Purpose: The aim of the study was the evaluation of image guided transdermal application of interstitial brachytherapy in patients undergoing repeated irradiation for relapsed local tumor of the head and neck area. Material and methods : The article describes transdermal application of interstitial high-dose-rate (HDR) brachytherapy in 4 patients treated due to relapsed local tumor in soft palate, submandibular area, laryngopharynx, as well as pterygoid muscles and maxillary sinus. The application was conducted under continuous computed tomography (CT)-image guidance (CT fluoroscopy). Patients qualified for this type of treatment had neoplastic lesions located deep under the skin surface. Because of their location, access to the lesions was limited, and the risk of damaging the adjacent tissues such as vessels and nerves was high. The following parameters have been evaluated: clinical response using RECIST 1.1, incidence of perisurgical complications using CTCAE 4.0 and the frequency of occurrence of radiotherapy related early morbidity using RTOG. Results: Various radiation schemes were used, from 3 to 5 fractions of 3.5-5 Gy. The median total dose (D90) was 20.6 Gy. Biologic effective dose (BED) and equivalent 2 Gy (DEQ2) median doses were 30.4 Gy and 25.3 Gy, respectively. In the follow-up period of 3-7 months (the median value of 3.5 months), 2 patients had partial regression of the disease and in 2 others the neoplastic process was stabilized. None of the patients had serious complications of treatment (of 3rd degree or higher). Conclusions : Computed tomography-image guided brachytherapy proved to be a safe method of treatment in patients with local relapse in sites, in which traditional visually controlled application was impossible due to risk of complications. Despite short observation period and small study group, it seems justified to conduct prospective studies for the evaluation of efficacy and safety of CT-image guided brachytherapy.